Experimental and numerical study on thermal protection by silica aerogel based phase change composite. (November 2020) - Yin, Huibin; Gao, Shiyuan; Cai, Zhuodi; Wang, Huixing; Dai, Liling; Xu, Yongjun; Liu, Jian; Li, Hong
Abstract: In this work, an incubator is developed for vaccine cold chain transport based on paraffin/SiO2 aerogel composite with polystyrene board for coupling packaging. The morphology and thermal property of PCM was characterized. A combined numerical and experimental study has been conducted to study the multi-level gradient heat transfer behavior. The coupling between the outer insulation board and the inner layer PCM can achieve great synergistic gain, it is reflected in the fact that maintain time increased by 99 times compared to the condition with only insulation board. The optimal double layer board configuration is optimized as XPS/PCM and the thickness ratio is determined as 1:3. The lifting rate of the holding time presented an increasing trend with the overall size of the incubator increasing, providing alternative basis for the cold chain transport configuration under different requirements.